2018
DOI: 10.1007/s40617-018-0270-8
|View full text |Cite
|
Sign up to set email alerts
|

Behavior-Analytic Approaches to Working with People with Intellectual and Developmental Disabilities who Develop Dementia: a Review of the Literature

Abstract: Behavior analysis has made contributions in the development of evidence-based interventions for people with intellectual and developmental disabilities (IDD), and there is a growing evidence base for behavior-analytic interventions for older adults with dementia. As there is an increased number of adults with IDD living to old age, and an increased prevalence of comorbid dementia in people with IDD, a review of the behavior-analytic contributions with this population is warranted. We searched Web of Science an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…For all the regression models 3 presented in Table 2 , statistically significant p-values represent distinct whilst statistically insignificant p-values represent commonalities in measures between CP and MCI. A recent study indicated that adults with intellectual and developmental disabilities are more likely to develop early dementia [ 54 ]. Hence, the association between CP and dementia might be driven by neurologic or intellectual comorbidities, rather than as a direct effect of CP.…”
Section: Methodsmentioning
confidence: 99%
“…For all the regression models 3 presented in Table 2 , statistically significant p-values represent distinct whilst statistically insignificant p-values represent commonalities in measures between CP and MCI. A recent study indicated that adults with intellectual and developmental disabilities are more likely to develop early dementia [ 54 ]. Hence, the association between CP and dementia might be driven by neurologic or intellectual comorbidities, rather than as a direct effect of CP.…”
Section: Methodsmentioning
confidence: 99%
“…ABA is an evidence-based therapy that utilizes techniques of behavior modification and environmental contingency management to promote the learning of social skills, language, academic skills, and independence. The use of individualized programs, functional behavior analysis, and strategies of modeling and reinforcement has been effective in developing skills in children with IDD [15,16].…”
Section: Behavioral Interventions Have Shown Effectiveness In Clinica...mentioning
confidence: 99%
“…Each of these articles was evaluated against the inclusion criteria and the seven dimensions of ABA to confirm they were behavior-analytic (see Table 1). We adapted this process from Lucock et al (2019). Following full-text screening, one paper was excluded from the review (Aaronson et al, 2021) due to not meeting all seven dimensions of ABA.…”
Section: Screeningmentioning
confidence: 99%